2020
DOI: 10.1002/dac.4495
|View full text |Cite
|
Sign up to set email alerts
|

IoTScal‐H : Hybrid monitoring solution based on cloud computing for autonomic middleware‐level scalability management within IoT systems and different SLA traffic requirements

Abstract: SummaryWireless sensor network (WSN) technologies have enabled ubiquitous sensing to intersect many areas of modern day living. The creation of these devices offers the ability to get, gather, exchange, and consume environmental measurement from the physical world in a communicating‐actuating network, called the Internet of Things (IoT). As the number of physical world objects from heterogeneous network environments grows, the data produced by these objects raise uncontrollably, bringing a delicate challenge i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…A data flow diagram (DFD) serves as a visual representation of the system's logical function, the direction of logical flow, and the logical transformation of data within the student information management system. It is a primary tool for expressing structural system analysis methods and employs graphical techniques to depict software models [26]. The accompanying data flow diagram does not include specific physical elements; instead, it solely describes the system's flow and processing of information.…”
Section: E Data Flow Diagram Of Information Management System For Col...mentioning
confidence: 99%
“…A data flow diagram (DFD) serves as a visual representation of the system's logical function, the direction of logical flow, and the logical transformation of data within the student information management system. It is a primary tool for expressing structural system analysis methods and employs graphical techniques to depict software models [26]. The accompanying data flow diagram does not include specific physical elements; instead, it solely describes the system's flow and processing of information.…”
Section: E Data Flow Diagram Of Information Management System For Col...mentioning
confidence: 99%
“…It is observed that the controller incrementally and proactively adjusts the servers based on the requirements. A cloud‐based monitoring solution for autonomic scalability management within IoT systems is described in Reference 61. It is a hybrid approach which combines traffic‐oriented and resource oriented mechanisms with adaptation actions.…”
Section: Related Workmentioning
confidence: 99%
“…The second optimization factor is the scalability that defines the ability of a device to adapt to the changes and ability to change based on IoT system's future needs. Zyane et al [151] suggested combining the traffic-oriented mechanism and the resource-oriented mechanism with adaptation actions using autonomous middleware for scalability management. This method, aimed to maximize the number of requests received by providing an acceptable QoS level and system performance.…”
Section: Remote Services Layermentioning
confidence: 99%